Censorship and Self-censorship of University Students on Instagram and TikTok - López Fraile, Luis Antonio; Alonso Guisande, Miguel Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study explores censorship and self-censorship of young university students on two of the most successful social networks: Instagram and TikTok. The research focused on how they perceive censorship on both platforms and how this perception translates into self-censorship behaviour. Similarities and differences perceived in both networks and which of them offers a more restrictive environment for freedom of expression are explored. Non-experimental research was carried out on a sample of 502 students. The results indicate a unanimous perception of censorship and a self-censorship response from young people.